2017
DOI: 10.1111/jomf.12410
|View full text |Cite
|
Sign up to set email alerts
|

Black Mothers' Perceptions of the Role of Race in Children's Education

Abstract: in Children's EducationMany Black parents consider racial climate and academic quality when thinking and making decisions about their children's schooling experiences. However, few studies have directly asked Black parents about the role they believe race will play in their children's schooling, if any. The authors interviewed 76 Black mothers (M age = 34; SD age = 6.67) of children entering first grade (M age = 6.13; SD age = 0.36), asking what role they believed race would play in their children's schooling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…Indeed, they sometimes pushed through discomfort (such as in the case of the White father who called for a racially conscious curriculum despite resistance by White heterosexual parents) out of awareness of the need to advocate on behalf of their children, who possessed even less power and whose well‐being would be affected by the (in)actions of the larger parent community. Such findings echo those of Williams, Banerjee, Lozada‐Smith, Lambouths, and Rowley (2017), who documented how Black mothers advocated on behalf of their children, regarding themselves as “protective agents” via their school involvement.…”
Section: Discussionsupporting
confidence: 75%
“…Indeed, they sometimes pushed through discomfort (such as in the case of the White father who called for a racially conscious curriculum despite resistance by White heterosexual parents) out of awareness of the need to advocate on behalf of their children, who possessed even less power and whose well‐being would be affected by the (in)actions of the larger parent community. Such findings echo those of Williams, Banerjee, Lozada‐Smith, Lambouths, and Rowley (2017), who documented how Black mothers advocated on behalf of their children, regarding themselves as “protective agents” via their school involvement.…”
Section: Discussionsupporting
confidence: 75%
“…As White parents of children of color, these parents often appeared aware of their limited ability to provide racial socialization, thus relying in part on the school community of peers and teachers to do so (Park, ; Samuels, ), unlike middle‐class Black parents who can “make up” for needed racial socialization at home (Vincent et al, ). Parents' emphasis on racial diversity often appeared to reflect attunement to the psychosocial benefits of exposure to other children of color and a desire to promote positive racial identity development via peer interactions (Williams et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For parents who are LG, adoptive, or have a child of color, such resources could represent racial diversity and family diversity—the presence of others who might mirror the child and create a sense of belonging (Butler‐Sweet, ; Park, ). Indeed, the racial composition of children's social contexts, including school settings (Benner & Crosnoe, ), impacts racial identity development and well‐being (Benner, Graham, & Mistry, ; Williams, Banerjee, Lozada‐Smith, Lambouths, & Rowley, ). Yet, LG adoptive parents may weigh the benefits of having same‐race peers against the reality that schools that are mostly attended by children of color are often in poorer communities or co‐occur with less‐valued aspects of diversity (e.g., more families on state assistance; Billingham & Hunt, ).…”
Section: Parents' School Decision‐making and Selectionmentioning
confidence: 99%
“…Cooper () found that Black mothers from low‐income and working‐class backgrounds viewed schools not as a meritocratic institution but “as sites of resistance where they try to prevent resource and pedagogical inequity from eroding their children's ability to attain the education they need to succeed in a competitive world” (p. 113). Similarly, in another qualitative study exploring Black parents' beliefs around the role of race in their child's education, mothers considered the school's racial composition as well as behaviors and views of school personnel, and they were keenly aware of the discrimination their children may face (Williams, Banerjee, Lozada‐Smith, Lambouths, & Rowley, ). The study participants were mothers of first graders, and even with young children new to the school system, parents were determined to intervene and advocate in the case that they perceived race as negatively shaping their children's' educational experience.…”
Section: Intersections Of Critical Consciousness and Critical Race Thmentioning
confidence: 99%